Profit and Capital Structure as Positive Signals Against Firm Value - Khoiro Yulida; I Nyoman Nugraha Ardana Putra (LP2M IAIN Palopo, 2026)
The mining sector on the IDX faces challenges such as commodity price volatility and downstream regulations, which impact firm value through capital structure and profitability decisions. This study aims to analyze the influence of profit and capital structure as positive signals on firm value for the 2022-2024 period, with profitability as a moderating variable. A quantitative causal associative approach was used, using a population of all mining companies on the IDX, and a sample of 54 companies through purposive sampling. Secondary data from financial statements were analyzed using SPSS multiple linear regression after classical assumption testing. The results show a significant negative effect of capital structure (β=-0.776, p=0.002), a significant positive effect of profitability (β=0.511, p=0.020), and a significant negative moderating effect (β=-0.246, p=0.048), with an R² of 28.4%. Conclusion: Profitability mitigates the negative impact of capital structure, strengthening signaling theory for optimal investment decisions.